Robust control for a tracking electromechanical system - Dana Karimtaevna, Satybaldina; Asylbekkyzy, Kalmаganbetova Zhuldyzay (Institute of Advanced Engineering and Science, 2022)
A strategy for the design of robust control of tracking electromechanical systems based on ?∞ synthesis is proposed. Proposed methods are based on the operations on frequency characteristics of control systems designed and developed using the MATLAB robust control toolbox. Determination of the singular values for a transfer matrix of the control system reduces the disturbances and guarantees its stability margin. For selecting the weighted transfer functions, the basic recommendations are formulated. The efficiency of the proposed approach is verified by robust control of an elastically coupled two-mass system whose parameter values are adjusted by matching them with the parameters of one of the supplied robots. The simulation results confirm that the proposed strategy of design of robust control of two-mass elastic coupling system using the ?∞ synthesis is very efficient and significantly reduces the perturbation of parameters of the controlled plant.